(untitled) (De Rebus Antiquis, 2020)
The relationship between Barbarians and the Roman Empire has never been a neutral subject, and much less it could be today, when the debate on ‘Europe’s Christian roots’ focuses on the meaning of its identity. This paper sets out the views prevailing in the historiography of recent decades but also it turns to the context of the events that afflicted the Roman Empire through the fifth century. There is in fact a different approch to the subject, between the catastrophic paradigm and the view of scholars who attempted to circumvent the role of the Barbarians, as if they were mere onlookers and not real actors of history. The great complexity of the period invites for deepening the analysis of regional peculiarities, studying those multiple and repeated collapses of the Empire, which during the fifth century still survived elsewhere, while people thought it was already fallen.